EFEKTIVITAS BUS TRANS PADANG SEBAGAI MODA TRANSPORTASI PUBLIK DI KOTA PADANG - Rezki Tri Ananda; Sri Mariya (JURNAL BUANA, 2020)
This study aims to determine the effectiveness of the Trans Padang Bus as a mode of public transportation in the city of Padang, which is seen from 5 aspects namely accessibility, capacity, timeliness, safety and comfort, as well as tariff or price. The data used consists of primary and secondary data. Primary data obtained through observation and structured interviews of 60 random passengers. While secondary data were obtained from literature studies and related institutions. The method used is a simple scoring technique with effectiveness class that is Effective, Quite effective, and Not effective. The results of this study found that the Trans Padang Bus as a mode of public transportation in the city of Padang is "effective" overall and for each variable. Percentage score of each variable includes Accessibility 96%, Capacity 89%, Timeliness 84%, Safety and comfort 93%, and Tariff or price 100%. The Tariff variable or price is the highest with a perfect score. This means that the tariff offered is effective and affordable. Conversely, the timeliness variable is the lowest among others but is still relatively effective. Perhaps this needs to be evaluated so that Trans Padang services will be more effective in the future.